VILLAGE FUND POLICY: MEASURING THE PROGRESS OF ECONOMIC DEVELOPMENT IN FOUR REGENCY IN THE TOBA CALDERA THROUGH THE VILLAGE DEVELOPMENT INDICATOR (IPD) AND VILLAGE BUILDING INDEX (IDM) - Amran Manurung; Erlina; Sirojuzilam; Suwardi Lubis (Universitas Efarina, 2022)
Economic development is a process of developing community capacity in the long term so that it requires proper and accurate planning in reducing economic inequality between cities and regencies. One of the indicators for measuring the success of economic development in 4 regencies, namely North Tapanuli, Toba, Humbang Hasundutan and Samosir, which are in the Toba Caldera Area as a center for the development of world Geopark tourism which has been designated by UNESCO as a world heritage from the geological aspect.The purpose of this research is to conduct a descriptive economic analysisof the progress of the economic aspects of the 4 districts in the Toba Caldera region through the 2018 Village Development Index (IPD), namely to become Disadvantaged - Developing - Independent districts. While the Developing Village Index (IDM) will explain 5 categories ofRegency achievements for the status of villages classified as Very Disadvantaged - Underdeveloped - Developing – Advanced - Independent to prove the implementation of the Village Fund policy.The results of the study show that the 4 districts resulting from the division of regional autonomy policies and Fiscal Decentralization in Indonesia plus the Village Fund, it turns out that in 2020-2021 there are no districts that are included in the category of Independent and Advanced IDM Status. However, there are 2 districts that are in the Developing category, namely Samosir Regency with an IDM achievement of 0.6275 which is ranked 301st nationally and 12th at the provincial level in North Sumatra for City Regency. Furthermore, Toba Regency with an IDM of 0.6268 ranks 314th nationally and14th province. Finally, Humbang Hasundutan Regency has an IDM of 0.60502 in the 347th and 15th ranks. While the parent district, before the era of Regional Autonomy, namely NorthTapanuli Regency, was only included in the IDM status category, it was still lagging behind with an achievement of only 0.5904 being ranked 358th nationally and 8th in the province.In the IPD category, North Sumatra Province only reached 56.82, below the Sumatra Island average of 60.02, and the national average IPD reached 59.36. Furthermore, for these 4 regencies below the national average, the Sumatra Island region and the Provinces namely North Tapanuli 55.04, Toba 56.20, Humbang Hasundutan 56.08 and Samosir 54.84. So there is still much to be achieved by the Government of the 4 Regencies in order to improve people's lives optimally, prosperously, fairly and evenly, where the central government has stimulated the Village Fund policy which increased in value in the last 5 years before the Covid- 19 pandemic.